A CONTROLLED RELEASE MICROSPHERE FORMULATION OF AN ANTI-DIABETIC DRUG AND CHARACTERIZATION OF THE MICROSPHERE - Chakra, Biplab Kumar; Karan, Saumen; Das, Biswajit; Debnath, Souvik; Chatterjee, Tapan Kumar (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: Here the objective of this study was to prepare and characterize sustained release metformin loaded microsphere formulation which was prepared by W1/O/W2 emulsion solvent evaporation technique. Methods: Guar gum and sodium alginate were used as a matrix building material, whereas ethyl cellulose was applied as a coating polymer. Here various formulations were prepared by changing the drug and guar gum ratio, and the subsequent drug entrapment efficiency (DEE) and drug release were compared and evaluated. Results: Scanning Electron Microscopy (SEM) studies revealed spherical particles with a smooth appearance. Fourier-transform infrared spectroscopy (FTIR) showed there was no interaction between the ingredients in the final formulation. X-ray Diffraction (XRD) studies showed the emergence of polymorphic forms in the final formulation. The drug entrapment in the final drug loaded microsphere formulations was varied from 30-66.78%. The drug release studies showed the continuous release of the drug through twelve hours. The optimized formulation (f2) found to release 71.5% of drugs at the end of the 12th hour following zero order release kinetics. Conclusion: The increase in gum concentration in the W1 phase, which enhances viscosity in the W1 phase, resulting in an increase in the drug entrapment up to an optimum level and a decrease in the release rate. So, it can prolong the action. So by using this tool, we can say that metformin loaded microsphere formulation would be a suitable pharmaceutical formulation for the treatment of diabetic patients in modern drug therapy for its prolonged action.Â Â